RANCANG BANGUN SISTEM PERSEDIAAN BARANG MENGGUNAKAN METODE WATERFALL DI TOKO OBAT CITRA CILODONG DEPOK BERBASIS MOBILE APPLICATION - Halim, Zuhri; Maulana Irsyad, Teuku Fadhil (Infotech: Journal of Technology Information, 2025)
Currently, inventory management systems are one of the most essential components in stores or warehouses. Toko Citra is a pharmacy located at Jl. Raya Asrama Divif 1 Kostrad, Cilodong, Kec. Cilodong, Depok City, West Java. Established in 2005, the store still relies on manual record-keeping for inventory and receipts, which often results in data entry errors. Additionally, during busy hours, employees are frequently overwhelmed when handling transactions. To address these issues, the researcher developed a system designed to manage stock and transaction data at the store. The system was built using the waterfall development method, with Kodular Creator as the application platform and Google Spreadsheet as the database. After development, the system was tested using black-box testing, including alpha testing by the researcher and beta testing by the store owner and employees. The results showed that the system functions properly and is suitable for daily use by the staff at Toko Citra.